Cross-cultural servanthood serving the world in Christlike humility - Elmer, Duane, 1943- (Downers Grove, Ill. : IVP Books, 2006)
The last thing we want to do in cross-cultural ministry is to offend people in our host cultures. Unfortunately, all too often our actions inadvertently communicate superiority, paternalism, imperialism and arrogance. How can we minister in ways that are received as true Christlike service? Cross-cultural specialist Duane Elmer gives Christians practical guidance for serving internationally with sensitivity and humility. With biblical exposition and cross-cultural awareness, he shows how our actions and attitudes often contradict and offend local cultural sensibilities. He offers principles and guidance for avoiding misunderstandings and building relationships in ways that honor host cultures.
Servanthood : basic perspectives. Servanthood : its burden and challenge ; Servanthood : choosing the towel or the robe ; Humility : posture of the servant -- Servanthood : the process. Openness : welcoming others into your presence ; Acceptance : communicating respect for others ; Trust : building confidence in relationships ; Learning : seeking information that changes you ; Learning : biblical foundations for change ; Understanding : seeing through the other's eyes ; Serving : becoming like Christ to others -- Servanthood : the challenges. The servant and leadership ; The servant and power ; The servant and mystery ; The servant model : Joseph.
Includes bibliographical references (p. 207-212).
Description based on print version record.
Keywords: Service (Theology); Jesus Christ -- Servanthood; Intercultural communication -- Religious aspects -- Christianity; RELIGION / Christian Ministry / Missions; Electronic books